Coupling coordination degree of entrepreneurship and green development with digital transformation in China - Yanqing Guo; Kuo Zhang; Jin Xu (Digital Economy and Sustainable Development)
Abstract As digital transformation moves towards the digital quantum leap, the digital green transformation of enterprises in China's economic “dual transformation and coordination” development model urgently needs entrepreneurship to become the internal energy of the digital quantum leap. Using panel data comprising Chinese provinces (cities and automotive regions) from 2012 to 2022, this paper explains and evaluates entrepreneurship from the perspective of coupling coordination. It empirically examines the coupling coordination effect of the entrepreneurship system on green development and then analyses the impact of its role on green development in digital transformation and quantum leap. There are three main research findings: (1) Except for Beijing, Guangdong, Shanghai, Tianjin, Zhejiang, and Jiangsu, the coordination of entrepreneurship coupling in other Chinese regions is relatively low. (2) Entrepreneurship coupling coordination plays a significant role in enhancing green development in all Chinese regions. (3) The effect of entrepreneurship coupling coordination on economic performance is more significant in the country's eastern, southern, and coastal parts than in the other areas. The research findings have important policy implications for improving regional economic performance through enhancing entrepreneurship coupling coordination in the new era of rapid digital transformation and quantum leap.